Addressing the Needs Of English for Non-Formal Students in Teacher Training and Education : An ESP Analysis - Utami, Siti Nur; Rafiah Nur; Salasiah Ammade; Ammang Latifa; Siti Hajar larekeng; Shakira B. Herman (Eduvelop: Journal of English Education and Development, 2024)
English for Specific Purposes (ESP) is one of the key courses in several faculties at the Muhammadiyah University of Parepare. Looking at the importance of ESP itself, it is a collection of data related to student interest in non-formal majors in the Faculty of Education and Sciences. The study used quantitative descriptive designs to analyze students' needs in English for Specific Purposes (ESP) courses. The study involved eight non-formal education students from semester one to semester six. Using the questionnaire as the main instrument, the study was able to collect relevant data from the students. According to the data from the questionnaires that have been disseminated, students can enhance their English language skills by learning English for Specific Purposes, and there are some opinions among students that in ESP teaching, the use of Indonesian as an introductory language has a considerable influence on their understanding of the language. Comprehensive analysis that uses TSA (target situation analysis), LSA (learning situation analysis), and PSA (present situation analysis) is a diagnostic process to assess the current condition, learning environment, and future needs of an organization or group to inform strategic planning and decision-making. The results of data analysis will provide valuable insights to develop a more effective curriculum and teaching methods that fit the needs of students at Muhammadiyah University of Parepare, and the results of learning English for Specific Purposes will have a lot of influence on the survival of the English language skills of students for application in their scientific field.